Survey Tingkat Keterampilan Teknik Dasar Passing Bola Basket pada Ekstrakulikuler di Sekolah Menengah Atas Kabupaten Bungo - Ahmad Nurkholis; Ikhsan Maulana Putra; Titis Wulandari (Master of Physical Culture and Recreation in Nusantara, 2025)
Abstrak: This research was motivated by the low performance of high school basketball teams in Bungo Regency, despite regular training. Observations revealed errors in basic passing techniques, suspected to be influenced by the quality of training, attitude, and physical condition. This study aimed to determine the passing skill levels (chest pass, bounce pass, and overhead pass) among students at SMAN 2 Bungo, SMAN 12 Bungo, and SMK Setih Setio 2 Bungo. The research method used a quantitative survey approach. The sample consisted of 49 athletes using a total sampling technique. Data were obtained through passing skills tests and analyzed descriptively. The results showed that the passing skill levels were generally in the "Good" category. SMAN 2 Bungo was stable with 60% chest pass, 55% bounce pass, and 55% overhead pass (category "Good"). SMAN 12 Bungo also performed "Good" with 75% chest pass ("Good"), 58.33% bounce pass ("Fair"), and 50% overhead pass ("Good"). Meanwhile, SMK Setih Setio 2 Bungo tended to rank "Fair" with chest passes of 52.94%, bounce passes of 52.94%, and overhead passes of 58.82%. It was concluded that basketball passing skills in Bungo Regency are classified as "Good," but intensive and continuous training programs are still needed to improve skills evenly across all schools.